2011
DOI: 10.1016/j.watres.2011.06.012
|View full text |Cite
|
Sign up to set email alerts
|

Persistence of microbial and chemical pig manure markers as compared to faecal indicator bacteria survival in freshwater and seawater microcosms

Abstract: Natural seawater and freshwater microcosms inoculated with pig manure were set up to determine the persistence of pig faecal microbial and chemical markers in these two types of surface water. The concentrations of Lactobacillus amylovorus, the Bacteroidales Pig-2-Bac 16S rRNA genetic marker, five stanols and the evolution of two ratios of stanols, R1 (coprostanol to the sum of coprostanol and 24-ethylcoprostanol) and R2 (sitostanol to coprostanol) were analyzed during two months along with the concentration o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
31
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 43 publications
(36 citation statements)
references
References 33 publications
(20 reference statements)
4
31
1
Order By: Relevance
“…The environmental conditions influencing the decay of mtDNA markers may be complex because other environmental factors (e.g., salinity and dissolved oxygen) can also affect the persistence of microbial genetic markers (Jeanneau et al, 2012;Marti et al, 2011;Okabe and Shimazu, 2007). For example, the Bacteroides and Bifidobacterium genetic markers can persist longer in salt water than in fresh water (Green et al, 2011;Jeanneau et al, 2012;Solecki et al, 2011), whereas oxygen can accelerate the decay of the markers (Marti et al, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…The environmental conditions influencing the decay of mtDNA markers may be complex because other environmental factors (e.g., salinity and dissolved oxygen) can also affect the persistence of microbial genetic markers (Jeanneau et al, 2012;Marti et al, 2011;Okabe and Shimazu, 2007). For example, the Bacteroides and Bifidobacterium genetic markers can persist longer in salt water than in fresh water (Green et al, 2011;Jeanneau et al, 2012;Solecki et al, 2011), whereas oxygen can accelerate the decay of the markers (Marti et al, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…The shorter survival times (2 to 15 days) reported in these studies can be attributed to various physical and biological factors, including dissolved oxygen and predation, which have been implicated in shortening the persistence of strictly anaerobic Bacteroidales spp. (16,(19)(20)(21)(22)(53)(54)(55). Balleste and Blanch (22) suggested that environmental Bacteroides strains may be more sensitive to dissolved oxygen than pure cultures of Bacteroidales spp.…”
Section: Discussionmentioning
confidence: 99%
“…Separately, Lactobacillus amylovorus GE39/GE40, another pig-associated marker (19), was quantified at concentrations ranging from 4.6 to 6.5 log 10 copies/100 ml in 5 out of the 5 water samples collected downstream of the accidental spillage monitored in the present study (Olivia Solecki, Irstea, Rennes, France, personal communication). This marker has a greater persistence than Pig2Bac in fresh and marine waters (32) and might be considered for pig manure tracking at the catchment level. Correlation between the general Bacteroidales marker AllBac and the fecal indicators E. coli and enterococci has been previously reported (11).…”
Section: Discussionmentioning
confidence: 99%